Surgical Treatment of Carotid-cavernous Fistula Performed through the Brazilian Unified Health System - Luna, Ilanna Sobral de; Costa, Airan Lobo da (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Introduction The carotid-cavernous fistula (CCF) is an abnormal communication between the arterial carotid system and the cavernous sinus. In most cases, spontaneous fistulas are due to the rupture of intracavernous carotid artery aneurisms. Traumatic fistulas occur in 0.2% of head injuries, and 75% of all CCFs are caused by automobile accidents or penetrating traumas.Objective To identify the data regarding the number of annual procedures, hospital expenses, length of hospital stay, and the number of deaths of patients admitted by the Brazilian Unified Health System (SUS, in the Portuguese acronym), in the period between 2007 and 2017, using the surgical code of the surgical treatment for CCF.Methods The present was an ecological study whose data were obtained by consulting the database provided by the Department of Computer Sciences of the Brazilian Unified Health System (Datasus, in Portuguese).Results A total of 85 surgical procedures were performed for the treatment of CCFs from January 2007 to October 2017 through the Unified Health System (SUS, in Portuguese), and there was a reduction of 71.42% in this period. The annual incidence of patients undergoing this surgical treatment during the period observed remained low, with 1 case per 13,135,714 in 2007, and 1 case per 51,925,000 in 2017.Conclusion Despite the low annual incidence of the surgical treatment of CCFs performed by the SUS in Brazil in the period of 2007–2017, based on the data obtained on the average length of stay and expenditures in hospital services, it is necessary that we develop an adequate health planning.
Keywords: carotid-cavernous fistula; Brazilian unified health system; health care